English biography in the seventeenth century : a critical survey - Pritchard, Allan (University of Toronto Press, 2005)
"After charting the growth of seventeenth-century biographical writing, Pritchard explores the ways in which traditional forms of religious biography and lives of princes and other secular figures were adapted to, and transformed by, the crises and revolutions of the period. He then considers the development of less traditional biographical types and analyses the emergence of a 'new biography, ' concerned essentially with individuality and with private as well as public life."--Jacket